The first Zionist Congress : an annotated translation of the proceedings - Reimer, Michael J. (State University of New York, 2019)
An indispensable primary source in the history of Zionism. The First Zionist Congress, held in Basel, Switzerland, in August 1897, was arguably the most significant Jewish assembly since antiquity. Its delegates surveyed the situation of Jews at the end of the nineteenth century, analyzed cultural and economic issues facing them, defined the program of Zionism, created an organization for planning and decision-making, and coalesced in camaraderie and shared aspiration. Though Zionism experienced multiple conflicts and reversals, the Congress's goal was ultimately realized in the establishment of Jewish sovereignty in Palestine--the State of Israel--in 1948. As Theodor Herzl, the Congress's principal organizer, declared: "At Basel I founded the Jewish state." This volume presents, for the first time, a complete translation of the German proceedings into English. Michael J. Reimer's accessible translation includes explanatory annotations and a glossary of key terms, events, and personalities. A detailed introduction situates the First Zionist Congress in historical context and provides a summary of each day's events. The Congress's debates supply a case study in the history of nationalism: they feature imagery and tropes used by nationalists all over Europe, while appealing to the distinctive heritage of Judaism. The proceedings are also important for what they say--and omit--about the Ottoman state that ruled Palestine as well as the Palestinian Arab people living there. This is a foundational primary source in modern Jewish history. Michael J. Reimer is Associate Professor of History at the American University in Cairo. He is the author of Colonial Bridgehead: Government and Society in Alexandria, 1807-1882